PRANK CREATIVITY IN ADVERTISING - Almira Anindita; Andayu Farah Devani; Ade Kusuma (JOSAR (Journal of Students Academic Research), 2021)
Nowadays, the prank phenomenon is viral. It is often used for social media content as humor to entertain the audience. The prank displays the audience's expressions and shock by the joke. Several Indonesian YouTubers have shown the pros and cons when the video content of prank displays lies and harms others. The concept of prank also created criticism and sentiment from the public. The phenomenon of Gantung Panci by Indonesian culinary figure, Sisca Soewitomo, was viral on social media and attracted the netizens who felt entertained by the creative content of the GoFood ad. This study aims to see how digital workers accept and interpret creative jokes based on advertising. This study used a qualitative descriptive method with the encoding-decoding reception model analysis approach from Stuart Hall. The data was collected using in-depth interviews with digital workers, observation, documentation, and literature study. The results of this study show how the backgrounds and interpretations of digital workers in a dominant, negotiate, and opposition position uses the creative content of the prank by GoFood Ads ‘Mrs. Sisca Gantung Panci’. This research also finds out how creative advertising strategies in the digital era increase brand awareness and brand engagement of a product.